Microwave dielectrics in the (La1/2Na1/2)TiO3-Ca(Fe1/2Nb1/2)O-3 system - Kim, HJ; Kucheiko, S; Yoon, SJ; Jung, HJ (AMER CERAMIC SOC, 1997)
Dielectric properties of the system (1 - x)(La1/2Na1/2)TiO(3)x-Ca(Fe1/2Nb1/2)O-3, where 0.4 less than or equal to x less than or equal to 0.6, have been investigated at microwave frequencies, The temperature coefficient of resonant frequency (tau(f)), nearly 0 ppm/degrees C, was realized at x = 0.58. These ceramics had perovskite structure and showed relatively low dielectric losses. A new dielectric material applicable to microwave devices having Q.f of 12000-14000 GHz and a dielectric constant (epsilon(r)) of 59-60 has been obtained at 1300-1350 degrees C for 5-15 h sintering.
Keywords: FREQUENCIES; CERAMICS; PEROVSKITE; RESONATOR